Bystander Efforts and 1-Year Outcomes in Out-of-Hospital Cardiac Arrest - Kragholm, Kristian; Wissenberg, Mads; Mortensen, Rikke N; Hansen, Steen M; Malta Hansen, Carolina; Thorsteinsson, Kristinn; Rajan, Shahzleen; Lippert, Freddy; Folke, Fredrik; Gislason, Gunnar; Køber, Lars; Fonager, Kirsten; et al. (The New England journal of medicine, 2017)
Among patients in Denmark who survived for 30 days after out-of-hospital cardiac arrest, bystander CPR and bystander defibrillation were associated with significantly lower risks of brain damage or nursing home admission and of death from any cause than no bystander intervention.